Breaking the Cycle: A Medicolegal Analysis of the Effectiveness of Interventions in Preventing Domestic Violence Recidivism in Dhaka, Bangladesh - Mohammed Ayash; Shahlia Khan (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Domestic violence remains a pervasive issue globally, and Dhaka, Bangladesh, is no exception. This study aimed to examine the effectiveness of various interventions in preventing recidivism among domestic violence perpetrators in Dhaka. Methods: A retrospective cohort study was conducted involving 300 individuals convicted of domestic violence between 2018 and 2023 in Dhaka. Data were collected from court records, police reports, and intervention program records. Recidivism was defined as a subsequent conviction for domestic violence within three years of the initial conviction. The impact of interventions, such as batterer intervention programs, counseling, and legal sanctions, on recidivism rates was analyzed using Cox proportional hazards regression models. Results: The overall recidivism rate was 32%. Participation in batterer intervention programs was associated with a significant reduction in recidivism (Hazard Ratio [HR] 0.52, 95% Confidence Interval [CI] 0.35-0.77). Counseling also demonstrated a modest protective effect (HR 0.71, 95% CI 0.53-0.95). Legal sanctions, such as restraining orders and probation, were not independently associated with reduced recidivism. Conclusion: Batterer intervention programs and counseling show promise in reducing domestic violence recidivism in Dhaka. A multi-pronged approach incorporating these interventions, along with enhanced legal and social support systems, is crucial for effectively breaking the cycle of domestic violence.